Editorial Note - Nzaka Munga, Cosmas (Multidisciplinary Journal of Technical University of Mombasa, 2025)
Editorial NoteWe would like to thank all our authors and co-authors who contributed to the  successful release  of this Volume 4 Issue 1 of MJTUM. There are a total of 9 publications from different authors and co-authors within and outside Kenya, out of these 6 are research articles and 3 are review articles. These published articles cover a diverse array of fields ranging from information and computer science, communication science, architecture and built environment, artificial intelligence and cyber security, gender in seaweed mariculture, engineering and technology to accounting and finance. The content of all the articles is as a result of dedicated research works from the authors and co-authors. MJTUM is hereby providing a platform to share the contents of these research and review works in contributing to knowledge dissemination to the scientific community and to all students in their quest to advance knowledge in their respective fields. MJTUM will continue to provide a platform for dissemination of high quality scholarly articles. It is my sincere hope that you will enjoy reading the wide scope of these published articles in this current issue as we prepare you for the release of Issue 2 of Volume 4.